Middle-term field research on air and noise pollution in the city district of Baltic region - Chlebnikovas, Aleksandras; Bradulienė, Jolita (International Conference “Environmental Engineering”, 2023)
Air quality monitoring, as well as physical pollution, in particular noise, is an important component for assessing the quality of life in cities and their regions. Detailed and accurate studies require an analysis of the results obtained with at least an average time interval, which was carried out in this study of the environmental situation in the area of the city of the Baltic region. The results obtained can identify the main areas of greater pollution, enabling new planning of communication systems in small towns, as well as avoiding negative effects on the body of residents, thereby improving overall health. The data was obtained using a mobile laboratory and high-precision equipment, based on international standards for parameter measurement techniques. According to the results of the research, trends were found to reduce particulate matter up to 10 microns, depending on the seasons, by more than 10%. The noise level in most of the area remains unchanged, or gradually increases due to large traffic flows. In contrast to the recreational area, the greatest increase in pollution in the residential area found PM10, NO2 and benzene, by 30%, 39% and 72% respectively. In the area adjacent to the road infrastructure, concentrations of benzene, ethylbenzene and toluene were 37–54% higher than in the recreational area. The average concentrations of other pollutants were lower.